ENTRE LUTAS E ESPERANÇAS: os povos do campo e os projetos societários emancipatórios na América Latina - Maria Gorete de Sousa (Universidade Federal do Maranhão, 2018)
To build an alternative social project to capitalism from the periphery is essential to take up the critical Latin American thought. In the twenty-first century, within the wave of progressive governments, many expectations were raised by the workers’ movement, however for most of these governments the rupture was not put but a compromise that strengthened the civilizing model of capital, increasing violence in the cities and the countryside. We are at a historical crossroads in times of the structural crisis of capital, yet the experiences of the struggles and uprisings of the workers, indigenous, quilombolas, extractivists, and peasants present themselves as distinguishing marks of resistance and emancipatory possibilities.